Complex assembly, crystallization and preliminary X‐ray crystallographic analysis of the chicken CD8αα–BF2*0401 complex. Issue 9 (1st September 2014) - Liu, Yanjie; Chen, Rong; Tariq, Mansoor; Xia, Chun
<x xml:space="preserve">Abstract</x> In the process of antigen presentation, the MHCI–CD8 complex is important for immune signal transduction by the activation of cytotoxic T cells. Here, the expression, purification, crystallization and X‐ray analysis of the complex of the chicken MHC class I molecule BF2*0401 and CD8αα (CD8αα–BF2*0401) are reported. This complex was verified by SDS–PAGE analysis of a CD8αα–BF2*0401 crystal, which showed three bands corresponding to the molecular weights of BF2*0401, β2‐microglobulin and CD8α, respectively. The crystal of CD8αα–BF2*0401 diffracted to 2.8 Å resolution and belonged to space group P21, with unit‐cell parameters a = 90.6, b = 90.8, c = 94.9 Å, β = 98°. The Matthews coefficient and solvent content were calculated to be 2.88 Å3 Da−1 and ∼57.3%, respectively.